Advanced financial accounting and reporting : for accounting students and CPA Reviewees - Punzalan, Angelito R.; Laco, Reginald L.; Ferrer, Rodiel C. (Manila : GIC Enterprises & Co. Inc., 2020)
This book was prepared according to the CPA Licensure Examination Syllabus in Advanced Financial Accounting and reporting.
CHAPTER 1. Partnership -- 2. Joint Arrangements -- 3. Accounting for Home Office, Branch and Agency -- 4. Accounting for business combination -- 5. Consolidated and Separated Financial Statements -- 6. Corporate Liquidation -- 7. Cost Accumulation and Job Order Costing -- 8. Process Costing -- 9. Accounting for Joint and By-Product Costing -- 10. Standard costing -- 11, Activity - Based and Just-In-Time/ Backflush Costing -- 12. Revenue from Contracts with Customers -- 13. Long-term Construction Contracts -- 14. Consignment Sales -- 15. Franchise Operations -- 16. Installment Sales -- 17. Accounting for Insurance contracts -- 18. Accounting for build, Operate and Transfer -- 19. Foreign Currently transactions and Translations of Foreign Currency -- 20. Accounting for Not-for-Profit Organizations -- 21. Government Accounting.
Keywords: ACCOUNTING